2016
DOI: 10.1016/j.conb.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-dependent adolescent organization of socio-sexual behaviors in mammals

Abstract: The adolescent transition from childhood to adulthood requires both reproductive and behavioral maturation as individuals acquire the ability to procreate. Gonadal steroid hormones are key players in the maturation of behaviors required for reproductive success. Beyond activating behavior in adulthood, testicular and ovarian hormones organize the adolescent brain and program adult- and sex-typical expression of sociosexual behaviors. Testicular hormones organize sexual and agonistic behaviors, including social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 39 publications
2
64
0
1
Order By: Relevance
“…However, more recent conceptualizations point to a second organizational wave that occurs during puberty (see Gur and Gur, this issue and Schulz and Sisk, this issue; Sisk, 2016). Animal models have demonstrated that both specific reproductive behaviors and non-sexual social behaviors such as dominance and play with conspecifics and parental behavior in adulthood are critically dependent on presence of gonadal hormones during the developmental period that comprises adolescence.…”
Section: Heightened Emotionality In Adolescence: Form and Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, more recent conceptualizations point to a second organizational wave that occurs during puberty (see Gur and Gur, this issue and Schulz and Sisk, this issue; Sisk, 2016). Animal models have demonstrated that both specific reproductive behaviors and non-sexual social behaviors such as dominance and play with conspecifics and parental behavior in adulthood are critically dependent on presence of gonadal hormones during the developmental period that comprises adolescence.…”
Section: Heightened Emotionality In Adolescence: Form and Functionmentioning
confidence: 99%
“…For example, patterns of peer interaction and sexual behavior during early adolescence tend to persist into adulthood (Dishion et al, 2012; Sisk, 2016) and adoption of group social norms and group culture tends to be much more profound during childhood and adolescence than during adulthood (Cheung et al, 2011). Furthermore, at a mechanistic level, many of the processes that underlie brain maturation can also mediate learning across the lifespan.…”
Section: Heightened Emotionality In Adolescence: Form and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, puberty and adolescence appear to be closely linked, considering that the brain constitutes a target organ that responds to the presence of a number of hormones whose concentration increases during puberty. To date, solid evidence suggests that gonadal hormones have a different influence on the socio-sexual behavior of men and women during adolescence (Sisk 2016). Thus, during male adolescent development, testosterone programs the ability to make behavioral adaptations to social experience that improve reproductive efficience and avoid aggression, leading to better reproductive fitness.…”
Section: Brain Developmental Windowmentioning
confidence: 99%